1993
DOI: 10.1111/j.1744-7348.1993.tb04038.x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to potato leafroll luteovirus can be greatly improved by combining two independent types of heritable resistance

Abstract: Twelve potato clones were exposed to infection by aphids with potato leafroll luteovirus (PLRV) in three field trials in order to assess their resistance to infection. Up to 92% of the plants of some clones became infected, although other clones were relatively resistant to infection and one clone remained virusfree in all three trials. The resistance of the same 12 clones to PLRV multiplication was assessed in glasshouse-grown plants: plants were graft-inoculated and their daughter tubers were used to grow pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 10 publications
1
17
1
Order By: Relevance
“…This raises the possibility that this resistance to infection could after all be due at least partly to the same mechanism as the resistance to accumulation, although the two types of resistance can occur separately (Solomon-Blackburn & Barker, 1993). However, only very rarely did PLRV move into other parts of aphid-inoculated G8107(1) plants: we were unable to detect PLRV in their petiole or stem tissues by ELISA, immunoprinting or return graft assay; secondary infection was detected in only two tuber progenies of 33 tested (one from a plant inoculated with 100 aphids and one from a tuber with sprouts inoculated with 25 aphids).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This raises the possibility that this resistance to infection could after all be due at least partly to the same mechanism as the resistance to accumulation, although the two types of resistance can occur separately (Solomon-Blackburn & Barker, 1993). However, only very rarely did PLRV move into other parts of aphid-inoculated G8107(1) plants: we were unable to detect PLRV in their petiole or stem tissues by ELISA, immunoprinting or return graft assay; secondary infection was detected in only two tuber progenies of 33 tested (one from a plant inoculated with 100 aphids and one from a tuber with sprouts inoculated with 25 aphids).…”
Section: Discussionmentioning
confidence: 99%
“…We therefore suggest that an important element in the very strong resistance of this clone to PLRV is resistance to virus movement within or from the leaves. Pentland Crown (Solomon-Blackburn & Barker, 1993). Mihovilovich et al (2007) also suggested that a single mechanism might account for both of these two types of resistance in S. tuberosum ssp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minor genes for resistance are probably derived from S. demissum and S. acaule, as well as from other natural sources (Uhrig et al 1992). A complex genetic control of resistance means that the identification of the most resistant genotypes among the progeny of crosses between resistant and susceptible parents is not straightforward (Barker and Harrison 1985;Solomon-Blackburn and Barker 1993), although the resistance ratings of cultivars can be derived from the results of field experiments (Davidson 1973).…”
Section: Breeding For Resistance To Plrvmentioning
confidence: 99%
“…Resistance to infection by aphid transfer and resistance to titre build-up after graft challenge were found to be distinct traits that were not necessarily correlated when assessed as secondary infection (e.g. indexed in foliage grown from the daughter tubers of inoculated plants) in advanced breeding clones (Solomon-Blackburn and Barker 1993). Resistance to titre build-up in the section Etuberosa was first described by Jones (1979) for S. brevidens Phil, and in somatic hybrids with cultivated potato by Austin et al (1985).…”
mentioning
confidence: 96%